Data Reduction Method for Synthetic Transmit Aperture Algorithm - KARWAT, Piotr; KLIMONDA, Ziemowit; SĘKLEWSKI, Michał; LEWANDOWSKI, Marcin; NOWICKI, Andrzej (Archives of Acoustics, 2010)
Ultrasonic methods of human body internal structures imaging are being continuously enhanced. New algorithms are created to improve certain output parameters. A synthetic aperture method (SA) is an example which allows to display images at higher frame-rate than in case of conventional beam-forming method.Higher computational complexity is a limitation of SA method and it can prevent from obtaining a desired reconstruction time. This problem can be solved by neglecting a part of data. Obviously it implies a decrease of imaging quality, however a proper data reduction technique would minimize the image degradation.A proposed way of data reduction can be used with synthetic transmit aperture method (STA) and it bases on an assumption that a signal obtained from any pair of transducers is the same, no matter which transducer transmits and which receives. According to this postulate, nearly a half of the data can be ignored without image quality decrease.The presented results of simulations and measurements with use of wire and tissue phantom prove that the proposed data reduction technique reduces the amount of data to be processed by half, while maintaining resolution and allowing only a small decrease of SNR and contrast of resulting images.